Health-promoting lifestyle behaviors and its association with sociodemographic characteristics in hospital clinical staff - Alireza Moghimi; Mohsen Saberi Isfeedvajani; Mohammad Javanbakht; Leila Khedmat; Leila Khedmat (Frontiers Media S.A., 2024)
ObjectiveThe aim of this study was to determine hospital clinical staff' health-promoting lifestyle behaviors, and explore associations between nurse demographic factors and lifestyle behaviors.MethodsThis cross-sectional investigation focused on the clinical personnel employed at hospitals associated with Baqiyatullah University. A sample of 341 clinical staff of hospitals was collected using convenience sampling. In this study, the questionnaire of Health Promoting Lifestyle Profile II (HPLP-II) was used to assess health-promoting behaviors.ResultsIn the present study, the mean HPLP score was 131 ± 23. The score of health-promoting behaviors was significantly higher in the nursing major (p = 0.029). Also, a difference was found between the major and the subscales of health responsibility (p = 0.000), stress management (p = 0.004), physical activity (p = 0.004) and nutrition (p = 0.001). The score of health responsibility, stress management, physical activity and nutrition subscales was higher in nursing. There was a significant relationship between education and stress management (p = 0.033) and physical activity subscales (p = 0.001). The physical activity score was also higher in individuals with master's and doctoral degrees, and the stress management score was higher in participants with master's degrees. Based on the findings presented herein, age (p = 0.001) and gender (p = 0.016) were associated with the nutrition subscale, and the nutrition score was higher in the age group of over 30 years and in women. Additionally, a significant relationship was observed between marriage and the subscales of spiritual growth (p = 0.013) and nutrition (p = 0.024), and the score of spiritual growth, and nutrition was higher in married people. There was a significant relationship between job and health responsibility (p = 0.013) and nutrition (p = 0.022), and the score of health responsibility and nutrition score was found to be higher in nurses.ConclusionHealth-promoting behaviors of hospital employees are at an average level and are related to the educational levels of the employees, so these behaviors are more in nurses, while this relationship was not present in physicians. These findings may be helpful in providing recommendations for developing healthy lifestyle programs for clinical staff aimed at promoting health behaviors.